Probability of Breech Presentation in Fetuses with Sirenomelia at Birth - Mina Maričić; Jelena Podgorac; Srđan Kesić; Branka Petković; Aleksandra Vejnović; Ivan Čapo; Slobodan Sekulić (Clinical and Experimental Obstetrics & Gynecology)
Background: The 50% maximum probability of breech presentation (BP) implies that the same number of fetuses/newborns with the same characteristics take either BP or cephalic presentation (CP) with equal probability. Sirenomelia offers the possibility to investigate the incidence of BP in the simultaneous presence of several medical entities, each associated with an increased incidence of BP (Potter anomaly, lower limb fusion, prematurity, additional medical entities). The aim of the study is to investigate the probability of BP at delivery in sirenomelic singleton gestations to confirm the rule that the maximum probability for BP is 50%. Methods: A systematic retrospective literature search using the keywords: sirenomelia, sympus apus, sympus monopus, and sympus dipus, in the SCOPUS database. Inclusion criteria: presentation of singleton fetuses at delivery in the second and third trimester of pregnancy. Comparison with chi-square test (level of significance p < 0.5) of overall incidence of BP and CP as well as depending on the type of sirenomelia, prematurity, presence of additional medical entities associated with increased incidence of BP. Results: In total, 67 articles were identified, and 83 cases were found. The number of cases in BP vs. CP with a statistical difference to expected 50%:50% distribution of presentations: All cases—BP44 CP39 p = 0.583; Premature birth—BP25 CP20 p = 0.456; Term birth—BP17 CP18 p = 0.866; Sympus apus—BP15 CP14 p = 0.853; Sympus monopus—BP6 CP9 p = 0.439; Sympus dipus—BP21 CP14 p = 0.237; With additional entities—BP16 CP10 p = 0.239; Without additional entities—BP23 CP26 p = 0.668. Also, there were no statistically significant differences in the distribution of presentations between premature and term birth (p = 0.589), three types of sirenomelia (p = 0.601), with and without additional entities (p = 0.228). Conclusions: This study supports the rule that the maximum probability for BP in any medical entity, including sirenomelia, is 50%. The outcome of the BP should be evaluated with the case-control matching procedure: subtract the number of fetuses/newborns from the CP group that is identical to the number of fetuses/newborns in the BP group, with identical characteristics, and add this group to the BP group before comparing them to the rest of the CP fetuses/newborns.